AB0200 Do ultrasound-guided corticosteroid injections provide short-term relief of symptoms in patients waiting total hip replacement?. (1st June 2001) - Karim, Z; Brown, AK; Connor, PJO; Quinn, M; Jackson, G; Wakefield, RJ; Conaghan, PG; Emery, P
Abstract : Background: Osteoarthritis is the commonest cause of total hip joint replacement. The indication for this procedure is pain and loss of function that has not responded adequately to conservative therapy. Maintaining good muscle strength and optimising weight are important to good outcome post-surgery. This is difficult when symptoms reduce patients? mobility. Corticosteroid injections are commonly used for short-term relief of joint symptoms. Objectives: The primary aim of this pilot study is to determine whether corticosteroid injections improve pain and function in this group, and to identify any baseline features that predict response. Methods: Patients with osteoarthritis or stable rheumatoid arthritis awaiting total hip replacement are invited to take part. Patients with a contraindication to intraarticular corticosteroid or impending replacement (within 3 months) are excluded. Baseline data collected includes the WOMAC index, VAS for pain and stiffness during rest and walking, and SF-36. These outcome measures are repeated at 2, 6 and 12 weeks. Patients have 40 mg triamcinolone with 2 mls of 1% lignocaine via ultrasound-guided injection into the hip. Degree of capsular distension, a possible marker of synovitis, is documented by US. Conventional radiographs of the affected hip are also obtained to assess degree of damage. Results: 6 patients have been recruited to date in this ongoing study. Pain scores and functional changes have improved. Our experience suggests those with capsular distension are more likely to respond. Conclusion: Any reduction in patient symptoms that improves pre-operative pain and mobility should improve patient well-being and could also improve outcome post-surgery. Any predictor of response would allow the application of more accurate risk-benefit assessment for this procedure.